Comparison of MRI and bolster hyperextension radiography in determining the flexibility of thoracic curves in Scheuermann kyphosis: a retrospective cross-sectional study. Issue 1 (21st January 2023) - Chehrassan, Mohammadreza; Shakeri, Mohammadreza; Nikouei, Farshad; Toulany, Mahtab; Faraji, Mitra; Habibollahzadeh, Ali; Ghandhari, Hasan
Abstract : Background: The flexibility of the thoracic curve is important for the preoperative planning for patients with Scheuermann kyphosis (SK), and a lateral bolster hyperextension radiograph (HE) is the standard available method for this purpose. In this study, the authors aimed to evaluate how the flexibility of the thoracic curve in classic SK patients correlates between supine MRI and HE radiography. Methods: In a retrospective cross-sectional study, 38 SK patients who underwent surgical correction were included. Cobb angles were measured on three different images: lateral standing radiographs (EOS), lateral supine bolster HE radiography, and T2-weighted sagittal MRI. The mean differences between the Cobb angles measured on standing radiographs (EOS) and supine modalities (HE and MRI) was considered as the flexibility of the thoracic curve. Measurements were done two times by two orthopaedic spine surgeons, and acceptable intraobserver and interobserver reliability was observed using an intraclass correlation coefficient test. Results: The study population included 23 (60.5%) male patients and 15 (39.5%) female patients with a mean age of 23.4±8.8 yr (range 13 to 48). The mean flexibility of the thoracic curve was 31±10.9 degrees (40.5%) on supine MRIs and 36.1±11.5 degrees (47.25%) on bolster HE radiographs. A significant correlation was observed between the mean flexibility of the thoracic curve on MRI and HE radiographs (r=0.601, P <0.001). Conclusions: Supine MRI can be regarded as a promising alternative to bolster HE radiography in determining the flexibility of thoracic curves in patients with classic SK. Level of Evidence: Level III